2006
DOI: 10.1002/hep.21020
|View full text |Cite
|
Sign up to set email alerts
|

Long-term lamivudine therapy for children with HBeAg-positive chronic hepatitis B

Abstract: C hronic hepatitis B is a significant global health care problem that affects more than 350 million people worldwide, resulting in approximately 1 million deaths each year. 1 Despite the widespread availability of an effective vaccine, large numbers of children are infected. People infected early in life who have evidence of ongoing viral replication are at the highest risk for development of progressive liver disease and are a major source of infection in others. 2 Treatment options for children are limited. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
106
1
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(113 citation statements)
references
References 16 publications
(26 reference statements)
4
106
1
2
Order By: Relevance
“…However, the incidence of YMDD mutations was high at 64%. The durability of response among the responders at year 1 was 89% at month 24 [54]. In a study of longer duration of therapy (median 33, range 14-66 months), response was achieved in the first 2 years and none thereafter.…”
Section: Predictors Of Lamivudine Resistance and Managementmentioning
confidence: 90%
“…However, the incidence of YMDD mutations was high at 64%. The durability of response among the responders at year 1 was 89% at month 24 [54]. In a study of longer duration of therapy (median 33, range 14-66 months), response was achieved in the first 2 years and none thereafter.…”
Section: Predictors Of Lamivudine Resistance and Managementmentioning
confidence: 90%
“…Most of the children enrolled in these studies had pretreatment baseline ALT > 2×ULN. On the other hand, Sokal et al have revealed that resistance rates were 49% and 64% in 2-year treatment and 3-year treatment, respectively [76]. These were similar or even higher than those of adults.…”
Section: How To Prevent Nucleos(t)ide Analogue Resistancementioning
confidence: 93%
“…Molecular mechanism of resistance in HBV genome is well known but the optimal length for children's treatment with lamivudine required to achieve a durable virological response has not been established [5].…”
Section: Introductionmentioning
confidence: 99%